Problemas de proceso y resultado relacionados con los medicamentos : evolución histórica de sus definiciones (2011)
ABSTRACT: To analyze the historical evolution of the concepts of Drug-Related Problems (DRP), Drugrelated utilization problems (DRUP) and negative clinical outcomes (NCO) in order to unify the terminology at the national and international level, since confusion has been observed regarding the definitions of problems of process (causes) and problems of outcome (effects). Such issue may interfere with and have a negative impact on therapeutic goals. Methodology: a narrative literature review using the Medline and SciELO electronic databases in order to obtain information including the following concepts and terms: drp, drup, nco. No restrictions by date of publication were set, and the search was carried out in Spanish and English. Results: no consensus regarding the terms used with drug-related problems was found in the documents. In Decree 2200/2005 (Colombia), DRP are problems of drug use and negative outcomes of medication. Likewise, NCO are the negative clinical outcomes of medication (effects), and the DRUP are the problems in drug usage (DRP preventable causes associated with medication errors). Conclusions: although there are a number of terms for defining drugrelated problems, there is no national or international consensus on them.